Poverty on Unstable Ground: Structures, Experiences, and Narratives in Portuguese Society: https://doi.org/10.60543/ts_iss.vi10.11637 ("Temas Sociais" Journal, 2026)
Poverty continues to be widely interpreted as a lack of income or as the result of individual life trajectories. Drawing on the metaphor of a house built on unstable ground, this article conceptualises poverty as a structural and multidimensional phenomenon produced through the interaction of economic and social inequalities, public policies, and power relations.The article takes the form of a theoretical essay grounded in a critical review of the literature and the analysis of national and international statistical indicators. It examines the main theoretical approaches to poverty, the instruments used to measure it, the Portuguese context, and the role of public policies in addressing social inequalities. The article argues that poverty is neither a natural condition nor an exclusively individual problem, but rather the outcome of structural mechanisms that generate and reproduce vulnerabilities. It concludes that tackling poverty requires integrated strategies that combine redistribution, the guarantee of social rights, the strengthening of the welfare state, and the reduction of social inequalities.
Keywords: Poverty; Inequalities; Neoliberalism; Social Policies; Citizenship